Epidemiological aspects of rheumatoid arthritis at the rheumatology service of "Hospital Central Fuerza Aerea del Peru" (HCFAP) 1976-1992 - Valencia, Julio (1995)
The aim of this descriptive, longitudinal and retrospective study was to determine epidemiological aspects of the classical rheumatoid arthritis in the Rheumatology Service of HCFAP between 1976 and 1992. Two hundred and six cases of classical rheumatoid arthritis were evaluated. The delay of the diagnosis was defined as the time from the onset of the symptoms to the diagnosis itself. There were 169 women (82.03%) and 37 men (17.97%). The mean age was 65 ± 14.43 years (mean ± DE) in men and 61 ± 14.44 years in women. Yhe larger on age group was 46-55 years old (23.30%) and the smaller 16-25 years old. On admission, 48.75 cases presented grade II function. Rheumatoid factor was positive in 70% (P<0,001). The increased frequency of new cases was recorded in 1988 (11.65%) and the decreased frequency in 1978 (2.42%). In the delay for reaching the incapacity, 52.38% was found to be in the interval of 0 - 5 years. In relation with occupation, 71.21% were housewives. We conclude that this results are agree with data presented in the national and international literature, and it is possible that the larger number of cases observed in 1988 is related to the adjusment of the American Rheumatology Association criteria in 1987.